Blue nevus of the oral cavity. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
Case report. A 12-year-old boy, who is followed up since birth because affected by epidermolysis bullosa simplex type Dowling-Meara, was controlled because during an examination his dentist noticed a blue discoloration on the gingival border covering the first premolar of the left mandibular arch. On physical examination, there was a blue patch, uniform in color, covering all the palatal surface of the above mentioned gingival border, with regular and well defined border, with the maximum width of 1,5 mm level with the central point of the lesion, but then thinning when going towards the anterior and posterior region of the tooth itself. The child had not undergone any dental treatment with amalgam and did not report any trauma in his recent history. The color of the lesion and its regular border led to diagnose blue nevus of the oral cavity. A conservative approach was decided. 2 years later the lesion was unchanged.